Planning open and closed-loop feeders with efficiency analysis (2015)
The evolution of distribution systems (DS) towards the smart-grid concept posses new challenges, triggered by the integration of distributed generation (DG) and the installation of new devices. These challenges raise the need to reconsider the traditional network operation during the planning stage, enabling the DS to be flexible to operate under different network configuration scenarios. In this paper we propose a DS planning methodology for the connection of support feeders in radial networks, explicitly considering reconfiguration options with open-and closed-loop operation. To this end, we propose an efficiency evaluation, based on Data Envelopment Analysis, to assess candidate feeders in terms of expansion costs, energy losses, and lines' chargeability, under a range of demand scenarios that include GD penetration. Additionally, we have developed a method to identify the main feeder in a radial system, obtaining a simplified version of the DS, better suited for analysis. Simulation results on a real urban DS show the effectiveness of the method to identify the best nodes in a main feeder to connect support feeders, further indicating how to divide the network into operation areas for an improved network performance.